2020
DOI: 10.3724/sp.j.1006.2020.93053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strip-till with staggered planting on yield formation and shoot-root characteristics of spring maize in irrigation area of Xiliaohe plain

Abstract: A field research was conducted in the Agricultural High-tech Demonstration Park in Horqin District of Tongliao, Inner Mongolia, using the maize variety Nonghua 101 with two cropping modes, including strip-till with staggered planting (seeding strip tillage, 15 cm + 45 cm narrow-double row staggered sowing, TGCW) and conventional tillage with equal row space (rotary tillage with row space of 60 cm, CK), and three planting densities (67,500 plants hm-2 , 82,500 plants hm-2 , and 97,500 plants hm-2) in 2017 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Specifically, we found that root length density increased significantly in the 10-30 cm soil layer with linear planting and N fertilization at 20 cm depth (LD20), and this result is consistent with a study by York et al [54] in the USA, where deep nitrogen fertilization was found to increase the root length density in maize. Additionally, our study results were consistent with studies by Jiang et al [12] and Zhang et al [25], where zigzag planting manner was found to increase the root length density. These studies are similar to our linear planting at 20 cm depth and zigzag planting treatments, and resulted in maize root length density increment.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Specifically, we found that root length density increased significantly in the 10-30 cm soil layer with linear planting and N fertilization at 20 cm depth (LD20), and this result is consistent with a study by York et al [54] in the USA, where deep nitrogen fertilization was found to increase the root length density in maize. Additionally, our study results were consistent with studies by Jiang et al [12] and Zhang et al [25], where zigzag planting manner was found to increase the root length density. These studies are similar to our linear planting at 20 cm depth and zigzag planting treatments, and resulted in maize root length density increment.…”
Section: Discussionsupporting
confidence: 93%
“…These studies are similar to our linear planting at 20 cm depth and zigzag planting treatments, and resulted in maize root length density increment. Zigzag planting changed the row spacing, which can regulate root growth and optimize spatial root distribution [25]. In zigzag planting, the root grows and reaches deep soil layers, which allows for the utilization of more space moisture, and nutrients that improve the growth and resistance of maize against pest, pathogen, and environmental extremities [55,56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations